Social and Economic Justice of Labour in India: A Critical Study - Ramesh Kumar Bharti (AG Volumes, 2026)
This chapter undertakes a comprehensive examination of the State of social and economic justice for labour in India, delving into the historical evolution of labour laws and their contemporary implications. This study scrutinizes the existing legal framework governing labour rights, assessing its effectiveness in ensuring equitable treatment and economic well-being for the workforce. Emphasizing the interconnected nature of social and economic dimensions, the analysis explores issues such as workplace equality, discrimination, wages, benefits, and working conditions. The chapter critically evaluates the strengths and weaknesses of current policies, identifying gaps and challenges in their implementation. It sheds light on the impact of globalization on labour rights, considering the evolving dynamics of the Indian economy. The role of affirmative action and social welfare programs in promoting social justice is explored, alongside an examination of economic factors affecting labour, including income inequality and informal labour. The recommendations provided aim to contribute to the ongoing discourse on labour rights, advocating for a more robust and inclusive legal framework. This critical study serves as a valuable resource for policymakers, scholars, and practitioners seeking a nuanced understanding of the social and economic dimensions of labour justice in India